2010
DOI: 10.4103/0970-0218.62564
|View full text |Cite
|
Sign up to set email alerts
|

Prescription analysis of pediatric outpatient practice in Nagpur city

Abstract: Background:Medication errors are probably one of the most common types of medical errors, as medication is the most common health-care intervention. Knowing where and when errors are most likely to occur is generally felt to be the first step in trying to prevent these errors.Objective:To study prescribing patterns and errors in pediatric OPD prescriptions presenting to four community pharmacies across Nagpur city and to compare the prescription error rates across prescriber profiles.Materials and Methods:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
54
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 9 publications
9
54
3
Order By: Relevance
“…This very high level of antibiotic prescription among children is also reflected in studies from other developing countries as shown by the 81.3%, 79%, 63.4% and 51.6% found in studies conducted in Sudan, India, Gambia and Bahrain (11,12,14,16). The reasons for this prescribing habit among prescribers may not be far-fetched; studies have shown that while the cause of most acute respiratory tract infections and diarrheal disease is indeed viral, many medical doctors and care-givers still treat with antibiotics (17,18).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This very high level of antibiotic prescription among children is also reflected in studies from other developing countries as shown by the 81.3%, 79%, 63.4% and 51.6% found in studies conducted in Sudan, India, Gambia and Bahrain (11,12,14,16). The reasons for this prescribing habit among prescribers may not be far-fetched; studies have shown that while the cause of most acute respiratory tract infections and diarrheal disease is indeed viral, many medical doctors and care-givers still treat with antibiotics (17,18).…”
Section: Discussionmentioning
confidence: 60%
“…Risk et al, in a study among children in Gambia, found a mean of 2.2 while results from two similar studies in India showed a mean of 2.5 and 2.9 (11). Drugs as injections were prescribed in 5.9%, slightly higher than 3.5% and 1.6% reported in other studies (12,14). Prescribing by generic name is one of the major points of rational prescribing as it promotes improved access and affordability.…”
Section: Discussionmentioning
confidence: 97%
“…14,18 This preliminary study has given an insight into the pattern of AMA prescribing upon which future intervention studies may be based to promote rational drug use. Antibiotic policy and standard treatment guidelines are being framed.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalosporins were maximally prescribed followed by aminoglycosides which is also the trend seen in another study done by Pandey AA on prescription analysis of paediatric outpatient practice in Nagpur city. 2,10 In the present study, the total antibiotics prescribed contains cephalosporin 152 (80%), aminoglycoside 18 (9%), quinolones 13 (7%), antibiotic combination 4 (2%), B-lactamase inhibitors 2 (1%), macrolide antibiotics 1 (1%) each. 80% of antibiotics prescribed was cephalosporin which include 99% of ceftriaxone and 1% of cefixime.…”
Section: Discussionmentioning
confidence: 99%